Biosynthetic origins of the isoprene units of 4-nerolidylcatechol in Potomorphe umbellata - Bergamo, Debora Cristina B. [UNESP]; Kato, Massuo Jorge; Bolzani, Vanderlan da Silva [UNESP]; Furlan, Maysa [UNESP] (FapUNIFESP (SciELO), 2005)
The biosynthetic origins of the isoprene units of 4-nerolidylcatechol (1), the major constituent of Potomorphe umbellata, have been studied through feeding experiments with [14C]- and [13C]-glucose, and with precursors of the mevalonic acid and triose/pyruvate pathways, namely, [2- 14C]-mevalonolactone and [U-14C]-glyceraldehyde-3- phosphate, respectively. The pattern of incorporation of label from [1- 13C]-glucose into 1 was determined by quantitative 13C NMR spectroscopy. The labelling pattern revealed that the additive was specifically incorporated, and that the isoprene units of the sesquiterpenoid moiety of 4-nerolidylcatechol were derived from both the mevalonic acid and the triose/pyruvate pathways. The results indicate that both plastidic and cytoplasmic pathways are able to provide isopentenyl diphosphate units for the biosynthesis of 1. ©2005 Sociedade Brasileira de Química.
Keywords: 4-nerolidylcatechol; Biosynthesis, sesquiterpenoid; Isopentenyl diphosphate; Piperaceae; Potomorphe umbellata